Physiotherapeutic interventions in multiple sclerosis across Europe: Regions and other factors that matter - Martinková, Patrícia; Freeman, Jenny; Drabinová, Adéla; Erosheva, Elena; Cattaneo, Davide; Jonsdottir, Johanna; Baert, Ilse; Smedal, Tori; Romberg, Anders; Feys, Peter; Alves-Guerreiro, Jose; Habek, Mario; et al. (Multiple sclerosis and related disorders, 2018)
BACKGROUND: A wide variety of interventions exists in physical therapy (PT), but knowledge about their use across different geographical regions is limited. This study investigated the use of PT interventions in people with multiple sclerosis (MS) across Europe. It aimed to determine whether regions differ in applying interventions, and explore whether factors other than regions play a role in their use. METHODS: In an online cross-sectional survey, 212 respondents from 115 European workplaces providing PT services to people with MS representing 26 countries (four European regions) participated. Cluster analysis, Pearson Chi-squared test and a Poisson regression model were used to analyze the data. RESULTS: Thirteen of 45 listed PT interventions were used by more than 75% of centers, while nine interventions were used by less than 25%. For 12 interventions, regions differed markedly in their use. Cluster analysis of centers identified four clusters similar in their intervention use. Cluster assignment did not fully align with regions. While center region was important, center size, number and gender of physical therapists working in the center, and time since qualification also played a role. Cluster analysis exploring the use of the interventions provided the basis for a categorization of PT interventions in line with their primary focus: 1. Physical activity (fitness/endurance/resistance) training; 2. Neuroproprioceptive "facilitation/inhibition"; 3. Motor/skill acquisition (individualized therapy led); 4. Technology based interventions. CONCLUSIONS: To our knowledge this is the first study that has explored this topic in MS. The results broaden our understanding of the different PT interventions used in MS, as well as the context of their use.
Keywords: Cross-Sectional Studies; roztroušená skleróza; Europe; Cluster analysis; Evropa; mužské pohlaví; regresní analýza; průřezové studie; techniky fyzikální terapie; Physical Therapy Modalities; Cluster Analysis; Multiple Sclerosis; ženské pohlaví; Humans; Multiple sclerosis; Physiotherapeutic interventions; Regression Analysis; Questionnaire survey; Physical therapy; Female; shluková analýza; lidé; Male